Message Design Animation In Elearning To Stimulate Students To Design Messages Using Technolog - Firmansah, Muhammad Lukman Haris (International Journal of Educational Research & Social Sciences, 2022)
This research is research and development by utilizing animation in e-learning to form new knowledge for students. In addition to knowledge, this research also develops students' skills in designing messages using technology. The results are in the form of videos, animations and blogs, these are the results of the use of ADDIE research and development designs. The ADDIE model is oriented to the competition and conditional audience. The competency results showed that the attendance of 30 students showed an average of 82%, assignments 76%, formative evaluation 82%, summative evaluation 86%, making papers 72%, discussion 88%, work results 86%, and presentations 82%. The ADDIE model also offers validation of the animation media used. The 3 validators showed that the categories were good for 1) The attractiveness and clarity of the message, 2) it was easy to understand both visually and auditory, 3) both the message relevance (systematic and structured). The reason this research was applied is that the use of animation is also used to support the presentation of teaching materials where during the pandemic, bold learning is applied. The use of animation is a lesson plan which is then continued with face-to-face learning with schynchronous zoom integrated with the Moodle application. The summative and formative scoring system uses a google form that is connected to Moodle using a link. In this study also assess the material from the animation of 3 validators in the form of story boards. The average results of the use of messages have a valid and contextual theoretical basis keywords.